‘We were the Guinea pigs’: Police uncertainty enforcing coronavirus regulations in the UK. - De Camargo, Camilla (International journal of law, crime and justice, 2023)
The regulations introduced under the UK's Coronavirus Act 2020 to help curb the spread of COVID-19 caused considerable confusion due to conflation between what was regarded as ‘guidance’ and what was ‘law’. The fast-paced nature of the pandemic meant that restrictions on public liberty and increased police powers to enforce the new ‘rules’ led to accusations of over-zealous enforcement behaviour of some officers, including a record number of Fixed Penalty Notices (FPNs) issued. This paper explores the experiences of police officers in a range of English police forces, using 28 h of qualitative interview data at two research points in time (2020 and 2022). The extracts presented here illustrate some of the challenges that officers faced enforcing the frequently changing rules and regulations during the COVID-19 pandemic in the UK.